Lower NK cell numbers in children with untreated juvenile dermatomyositis during the COVID-19 pandemic - Christopher Costin; Gabrielle Morgan; Amer Khojah; Marisa Klein-Gitelman; Lauren M. Pachman (Clinical Immunology Communications, 2023)
RNA viruses have been posited as triggers for Juvenile Dermatomyositis (JDM). The COVID-19 pandemic proved a unique opportunity to observe the effect of a novel RNA virus on JDM incidence and phenotype. We found the incidence of JDM increased from average of 6.9 cases per year from 2012 to 2019 to 9 cases per year from 2020 to 2021. We compared markers of disease activity in the patients diagnosed with JDM prior to and during the pandemic and found that patients diagnosed with JDM during the pandemic had significantly lower average NK cell counts 90.75(± 76) vs 163(±120) (P = 0.038) and NK cell percentage 3.63% (±2.3) vs. 6.6% (±4.1), (P = 0.008). Other markers of JDM did not significantly change. This study suggests that COVID-19 may be a viral trigger for JDM in selected cases and that NK cell dysregulation may be of particular interest in future research of virally triggered JDM.